The Effect of Nasal Surgery on Continuous Positive Airway Pressure Device Use and Therapeutic Treatment Pressures: A Systematic Review and Meta-Analysis. Issue 2 (1st February 2015) - Camacho, Macario; Riaz, Muhammad; Capasso, Robson; Ruoff, Chad M.; Guilleminault, Christian; Kushida, Clete A.; Certal, Victor
Abstract: Background: The relationship between nasal surgery and its effect on continuous positive airway pressure (CPAP) device therapeutic treatment pressures and CPAP device use has not been previously systematically examined. Study Objectives: To conduct a systematic review and meta-analysis evaluating the effect of isolated nasal surgery on therapeutic CPAP device pressures and use in adults with obstructive sleep apnea. Methods: MEDLINE, Scopus, Web of Science, and The Cochrane Library were searched through July 15, 2014. The MOOSE consensus statement and PRISMA statement were followed. Results: Eighteen studies (279 patients) reported CPAP data after isolated nasal surgery. Seven studies (82 patients) reported preoperative and postoperative mean therapeutic CPAP device pressures and standard deviations, which reduced from 11.6 ± 2.2 to 9.5 ± 2.0 centimeters of water pressure (cwp) after nasal surgery. Pooled random effects analysis demonstrated a statistically significant pressure reduction, with a mean difference of −2.66 cwp (95% confidence intervals, −3.65 to −1.67); P < 0.00001. Eleven studies (153 patients) described subjective, self-reported data for CPAP use; and a subgroup analysis demonstrated that 89.1% (57 of 64 patients) who were not using CPAP prior to nasal surgery subsequently accepted, adhered to, or tolerated it after nasal surgery. Objective, device meter-based hours of use increased in 33 patients from 3.0 ± 3.1 to 5.5 ± 2.0 h in the short term (< 6 mo of follow-up). Conclusion: Isolated nasal surgery in patients with obstructive sleep apnea and nasal obstruction reduces therapeutic CPAP device pressures and the currently published literature's objective and subjective data consistently suggest that it also increases CPAP use in select patients.